Transcriptional response of bean bug (Riptortus pedestris) upon infection with entomopathogenic fungus, Beauveria bassiana JEF‐007. Issue 2 (3rd September 2018) - Lee, Se Jin; Yang, Yi‐Ting; Kim, Sihyeon; Lee, Mi Rong; Kim, Jong Cheol; Park, So Eun; Hossain, Muktadir S; Shin, Tae Young; Nai, Yu‐Shin; Kim, Jae Su
Abstract: BACKGROUND: Entomopathogenic Beauveria bassiana has been used as a biocontrol agent for insect pests, but its effect at the molecular level on the hosts has not been studied in detail. Herein, we performed transcriptome analysis of bean bug, Riptortus pedestris (Hemiptera: Alydidae) in response to infection with a highly virulent strain of B . bassiana JEF‐007 ( Bb JEF‐007). RESULTS: Based on RNA‐seq data from R. pedestris infected with Bb JEF‐007 compared with non‐infected bean bugs, infection was assumed to strongly activate (i) the energy production pathway by expressing dehydrogenases, (ii) metabolic pathways by expressing secreted proteins, GTPase, MBF2 transcription factor family, pigment‐dispersing factor, antioxidants, and cuticle proteins, and (iii) the immune response pathway by expressing serine‐threonine kinase in Toll pathway of bean bug. CONCLUSION: We have established the platform for functional studies of the genes required for an immune response against entomopathogenic fungi like B. bassiana in the bean bug, R. pedestris . Moreover, this study also paves the way for genetic modification of B. bassiana to combat with the defense mechanism of R. pedestris . © 2018 Society of Chemical Industry Abstract : The fungal infection was assumed to strongly activate some of the insect pathways, such as: (i) energy production pathway, (ii) metabolic pathways, and (iii) the immune response pathway.